Inhibition of Novel Cetuximab Resistance Pathway Leads to Improved Outcomes in Head and Neck Cancer. (23rd August 2013) - Lajud, Shayanne A.; Nagda, Danish; Kumar, Sanjeev; Qiao, Peter; Zheng, Jun; O'Malley, Bert W.; Li, Daqing
Abstract : Objectives: 1) Determine if cetuximab resistance in head and neck squamous cell carcinoma (HNSCC) is regulated by increased nuclear translocation of Epidermal Growth Factor Receptor (EGFR) through an MRN‐dependent Akt phosphorylation pathway. 2) Determine if targeted inhibition of the MRN complex, a key mediator of DNA damage response, can improve cetuximab sensitivity in HNSCC. Methods: Two well‐characterized human HNSCC tumor cell lines, with differential resistance to cetuximab, were chosen for this study. Mirin, a novel molecular MRN inhibitor was used for this study. MTT and clonogenic assays were used to evaluate in vitro cytotoxicity. Western blot analysis was performed to evaluate protein expression. In vivo tumor growth was evaluated using molecular imaging. Results: As compared with sensitive cells, cetuximab resistant cells demonstrated increased MRN expression, increased Akt phosphorylation, and increased nuclear EGFR. The inhibition of MRN led to a dose‐dependent decrease in Akt phosphorylation and nuclear EGFR translocation. Furthermore, MRN inhibition synergistically enhanced the cytotoxic effect of cetuximab in resistant cells ( P < 0.01). Conclusions: The findings from this study suggest a novel cetuximab resistance pathway involving MRN‐mediated Akt phosphorylation, leading to increased nuclear translocation of EGFR. Furthermore, inhibition of MRN led to decreased Akt‐phosphorylation, subsequently decreasing nuclear EGFR translocation, a key molecular mechanism involved in cetuximab resistance. Based on this discovery, inhibition of this pathway may serve as an effective therapeutic approach for HNSCC patients resistant to cetuximab.